Pb exposure induces an imbalance of excitatory and inhibitory synaptic transmission in cultured rat hippocampal neurons. (March 2020) - Zou, Rong-Xin; Gu, Xiaozhen; Ding, Jin-Jun; Wang, Tiandong; Bi, Nanxi; Niu, Kang; Ge, Mengmeng; Chen, Xiang-Tao; Wang, Hui-Li
Abstract: An appropriate balance of excitatory and inhibitory synapse maintains the network stability of the central nervous system. Our recent work showed lead (Pb) exposure can inhibit synaptic transmission in cultured hippocampal neurons. However, it is not clear whether Pb exposure disrupt the balance of excitatory and inhibitory synaptic transmission. Here, primary cultured hippocampal neurons from Sprague-Dawley (SD) rats were exposed to Pb (0.2 μM, 1 μM, 5 μM, respectively) from Days in Vitro (DIV) 7 to DIV 12 for 5 days and the excitatory and inhibitory synaptic transmission was examined. Patch clamp recording results showed that distinct from exposures of 0.2 μM and 5 μM, 1 μM Pb exposure significantly increased the mIPSC frequency and decreased the mEPSC frequency, leading to a uniform inhibitory outcome. Further, the number of inhibitory presynaptic puncta was significantly increased after 1 μM Pb exposure, while the number of excitatory presynaptic terminals was decreased. In addition 1 μM Pb increased the glutamic acid decarboxylase (GAD65) expression and the surface GABAA receptor (GABAA R) clusters. This shift might potentiate the synthesis of GABA and enhance the surface distribution of postsynaptic GABAA R clusters in hippocampus neurons. Together, these data showed that Pb exposure disrupted the balance of excitatory and inhibitory synaptic transmission via abnormal GABAergic neurotransmission. Highlights: The effect of Pb on the excitatory and inhibitory synaptic neurotransmission is dose-dependent. 1 μM Pb exposure disrupted the balance of excitatory and inhibitory synaptic transmission in cultured hippocampal neurons. 1 μM Pb exposure increased the glutamic acid decarboxylase expression and the surface GABAA receptor (GABAAR) clusters. Pb exposure shifted the balance of excitatory and inhibitory synapses via promoting GABA synthesis and GABAAR clusters.